A symbiotic bacterium of Antarctic fish reveals environmental adaptability mechanisms and biosynthetic potential towards antibacterial and cytotoxic activities - Xiao, Yu; Yan, Fangfang; Cui, Yukun; Du, Jiangtao; Hu, Guangzhao; Zhai, Wanying; Liu, Rulong; Zhang, Zhizhen; Fang, Jiasong; Chen, Liangbiao; Yu, Xi (Frontiers in Microbiology, 2023)
Antarctic microbes are important agents for evolutionary adaptation and natural resource of bioactive compounds, harboring the particular metabolic pathways to biosynthesize natural products. However, not much is known on symbiotic microbiomes of fish in the Antarctic zone. Here we report the isolation and identification of a symbiotic bacterium Serratia myotis L7-1, that is highly adaptive and resides within Antarctic fish, Trematomus bernacchii. As revealed by genomic analyses, Antarctic strain S. myotis L7-1 possesses carbohydrate-active enzymes (CAZymes), biosynthetic gene clusters (BGCs), stress response genes, antibiotic resistant genes (ARGs), and a complete type IV secretion system which could facilitate competition and colonization in the extreme Antarctic environment. The identification of microbiome gene clusters indicates the biosynthetic potential of bioactive compounds. Based on bioactivity-guided fractionation, serranticin was purified and identified as the bioactive compound, showing significant antibacterial and antitumor activity. The serranticin gene cluster was identified and located on the chrome. Furthermore, the multidrug resistance and strong bacterial antagonism contribute competitive advantages in ecological niches. Our results highlight the existence of a symbiotic bacterium in Antarctic fish largely represented by bioactive natural products and the adaptability to survive in the fish living in Antarctic oceans.